Sound matters: The impact of auditory deprivation on movement precision in rowing - Schaffert, N.; Oldag, B.; Cesari, P. (European Journal of Sport Science, 2020)
Purpose of the study was to quantify the importance of auditory feedback for movement precision in elevated rowing task difficulty with elite athletes under normal and masked hearing conditions. It was hypothesized that rowing with masked hearing would reduce the precision of movement, particularly at the non-usual/less-preferred stroke frequencies (SF). Self-reported questionnaires helped to understand the difficulty of the task. Twenty rowers completed 2 × 1000 m-distance-blocks, each separated into 4 × 250 m, with increasing SF 18, 20, 22 24 strokes/minute once with normal and once with masked hearing. Precision was determined as the deviation between the SF target and the SF actually performed (DSF). Athletes` subjective perception was requested before and after the experiment. A 2 (hearing condition) × 4 (SF 18, 20, 22, 24) repeated measures ANOVA showed systematically larger DSF during masked hearing for all SFs compared to the DSF in the normal hearing condition (p < .01). Further, the highest DSFs were found for SF 18 and 24 in both hearing conditions (no interaction effect). The athletes` perception of the relevance of natural movement sounds for their rowing performance changed when evaluated before and after the experiment. Rowing without hearing was evaluated as mentally more demanding than physically. The results confirmed our initial assumptions and showed the relevance of natural auditory information for movement precision in rowing practice, even at a high level of expertise.